Meningkatkan Ketrampilan Membaca Permulaan Menggunakan Media Kartu Kata Di Kelas 1 Sd Negeri 4 Gunungan Kecamatan Manyaran - Trisayekti, Atik (Universitas Sebelas Maret, 2020)
The ability to read is very important for all students at every level of education. Because the ability to read is the initial capital to take part in learning, and is also a foundation for students before acquiring other knowledge. The purpose of this research is to improve early reading skills by using word card media in grade 1 SD Negeri 4 Gunungan. It was carried out at SD Negeri 4 Gunungan involving 16 students consisting of 9 female students and 7 male students in the 2020/2021 school year. This research includes planning, action, observation and reflection. Data collection is done by using observations and tests. The data analysis used is quantitative and qualitative. From the results of the study, it was found that there was an increase in students' initial reading skills from cycle 1 to cycle 2. In cycle 1 only 44% of students who completed got criteria B (Good), while in cycle 2 it increased to 69%. This increase occurred because the teacher made improvements to learning including learning methods and learning media. In this learning using word card media so that students more easily master the material quickly. Based on the results of this study,it can be concluded that the use of world card media can improve students’ initial reading skills at SD Negeri 4 Gunungan students.